Answer:
Proved
Step-by-step explanation:
The options are not given. So, I will solve from scratch
Given
[tex]\frac{secx-1}{tan x}= \frac{tanx}{secx+1}[/tex]
Required
Prove
Multiply the right-hand side by [tex]\frac{secx + 1}{secx + 1}[/tex]
[tex]\frac{secx-1}{tan x} * \frac{secx + 1}{secx + 1}= \frac{tanx}{secx+1}[/tex]
Apply difference of two squares on the numerator
[tex]\frac{sec^2 x - 1}{(tanx)(secx + 1)} =\frac{tanx}{secx+1}[/tex]
In trigonometry:
[tex]tan^2x = sec^2x - 1[/tex]
So, we have:
[tex]\frac{tan^2 x}{(tanx)(secx + 1)} =\frac{tanx}{secx+1}[/tex]
[tex]\frac{tan x * tan x}{(tanx)(secx + 1)} =\frac{tanx}{secx+1}[/tex]
tan x cancels out
[tex]\frac{tan x}{secx + 1} =\frac{tanx}{secx+1}[/tex]
Proved